Facile and Novel in-Plane Structured Graphene/TiO2 Nanocomposites for Memory Applications - E. M. Shehata; M. M. Ibrahim; M. R. Balboul (Advances in Condensed Matter Physics)
Here, we report a simple strategy for the preparation of graphene/TiO2 nanocomposite by UV-assisted incorporation of TiO2 nanosol in graphene oxide (GO) dispersion. The proposed method is facile and of low cost without using any photocatalysts or reducing agents; this can open up a new possibility for green preparation of stable graphene dispersions in large-scale production. X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy (TEM) have been used to characterize carefully the as-prepared composites and to confirm the successful preparation of the nanocomposites. The average crystallite size of TiO2 nanoparticles calculated from XRD pattern using Rietveld analysis is ~35 nm. TEM measurements show the adsorption of TiO2 onto graphene (G) sheets, which prevents the restacking of graphene sheets. Current-voltage and capacitance-voltage measurements were used to investigate the electrical resistive memory properties of GO, GO/TiO2, and G/TiO2 thin films. Observed results show hysteresis behavior due to the charge trapping and detrapping process, indicating that the prepared thin films exhibit an excellent resistance switching memory characteristic for G/TiO2 device.